THE IMPACT OF THE ISRAELI AGGRESSION 2023 AND WORK MOTIVATION ON THE WORK PERFORMANCE OF MEDICAL STAFF IN THE INDONESIAN HOSPITAL IN GAZA - Qunoo, Sohaib M A; Kadir, Abd Rahman; Toha, Muhammad (Scientia Integritas Utama, 2023)
Israel did not hesitate to destroy all places of worship, people’s homes, and even hospitals where people receive health care due to random air strikes on citizens in the Gaza Strip. It is also known that the Al-Shifa Medical Complex, which is the largest hospital complex in the Gaza Strip, was targeted, in addition to the Indonesian Hospital. In this research, we want to clarify the extent of the impact of this aggression on the motivation of workers in the Indonesian hospital and on the work environment concerning the hospital’s performance in receiving patients and those injured as a result of these brutal raids. A quantitative descriptive-analytical research design was used, which attempts to describe the nature and characteristics of the data or variables being examined. The research findings provide valuable insights into the factors influencing employee performance, with a focus on work motivation and work environment.